Depression following coronary artery bypass grafting surgery revisited - Nosratollah Pourafkari; Leili Pourafkari; Nader D Nader (KARE Publishing, 2016)
Summary- Coronary artery bypass grafting (CABG) is the most common cardiac surgical procedure. Depression is a frequent comorbidity in patients with ischemic heart disease that can affect the course of the disease and the process of recovery after CABG. Depression after CABG is more common in women and is an independent predictor of mortality in long-term. However, fewer than half of cardiologists ask about depression symptoms in their patients, and with screening measures not being routinely utilized, depression remains under-recognized in this patient population. Treatment of depression in patients with ischemic heart disease can be challenging, considering unwanted medication side effects and interactions. The present report is a review of risk factors, prognosis, prevention, and treatment of depression in patients following CABG.